Telopeptide β-CTx in multiple myeloma and monoclonal gammopathy of undetermined significance. Is it a new prognostic marker in the wait-and see strategy accepted for patients with MGUS? - Wierzbowska, Agnieszka; Janasik, Beata; Jarkowska-Kozłowska, Jadwiga (Contemporary Oncology/Współczesna Onkologia, 2002)
In case of diagnosis of monoclonal gammopathy of undetermined significance (MGUS) there is no specific treatment. However, as results from previous retrospective estimations, after different time periods, in about 1/3 of persons with MGUS the symptoms typical for proliferation of plasmocytes, are observed. It is still not known however, why in about 30% of patients with MGUS deformation in parent cells genom of precursor clon have progressed. Therefore in patients with MGUS the wait-and-see strategy has been applied. Protein and mineral products of the bone degradation which are excreted into body fluids have mode possible the estimation of increasing osteolysis. Telopeptyde β-CTx - C-end fragment of 1 chain type I collagen with epitope EKAHDGGR is a structurally specific marker of bone resorption. Telopeptyde β-CTx was assayed in the serum of 40 multiple myeloma (MM) patients in different clinical stages, 19 patients with MGUS and 20 healthy individuals. The β-CTx concentrations were compared with CRP and Cac. in all sera examined. Moreover in MM patients β-CTx concentration levels were compared with Il-6 and sIL-6R. We observed an elevated level of β-CTx above the upper reference limit in 45% of MM patients. The serum telopeptyde concentrations were significantly higher in MM patients than in MGUS patients (p=0.035) and in healthy controls (p=0.0002). There was also a significant correlation between the telopeptyde serum concentration in MM patients and clinical stage of disease according to DurieSalomon and radiological evaluation of bone lesions as well as the serum CRP, Cac. and sIl-6R levels. However, there was no significant difference between Cac. concentrations elevated in 27% of MM patients and Cac. concentrations in patients with MGUS as well as healthy persons. No difference between serum β-CTx, CRP and Cac. concentrations in MGUS patients compared with normal individuals was observed. Almost two times higher occurrence of increased β-CTx concentrations in comparison with frequency of hypercalcemia in MM patients and normal level o telopeptyde in 5/6 of MM patients with stable disease demonstrate that serum β-CTx may be sensitive indicator of current bone resorption dynamics.